A1_3 Breaking the Broom - Weightman, Louise; Farr, Sam; Syed, Muhammad Zaryab; Dakin, Henry (Physics Special Topics, 2021)
In this paper we have examined the forces that act on the broomstick in the children's book 'Room on the Broom'. We have calculated the maximum weight on a maple wood broomstick to be 83.33 kg. The ideal strength to support the witch and her friends was calculated to be 57 MPa.